Helminthic Parasites of Scavenging Chickens (Gallus domesticus) from Villages in Penang Island, Malaysia - Abdul Wahab Rahman; Hasber Salim; Mohd Shafiq Ghause (Tropical Life Sciences Research, 2009)
Sixty scavenging chickens from villages in Penang were examined for their state of nutrition or body condition and the presence of helminthic parasites. The majority of the chickens were of poor body condition. More than 66.7% (females) and 73.3% (males) belonged to the ‘below normal’ category of general body condition. A total of eight different helminth species were recovered from the trachea and the gastrointestinal tract of the various chickens. Four of the species were nematodes and the rest were cestodes. No trematodes were recovered from the chickens. The highest mean worm burden was recorded for the cestode Raillietina echinobothrida while the lowest was the nematode, Ascaridia galli. Enam puluh ekor ayam pembangkai dari beberapa kampung di Pulau Pinang diperiksa mengenai status nutrisi atau keadaan tubuh serta parasit helmint. Kebanyakan daripadanya menunjukkan keadaan tubuh yang kurang memuaskan di mana 66.7% (ayam betina) dan 73.3% (ayam jantan) dimasukkan ke dalam kategori ‘di bawah normal’. Sebanyak lapan spesies helmint berlainan diperolehi daripada trakea dan saluran gastrousus. Empat daripada spesies tersebut adalah nematod dan selainnya adalah sestod, manakala tidak satu trematod pun diperolehi daripada ayam-ayam tersebut. Tanggungan purata cacing yang tertinggi direkodkan untuk sestod Raillietina echinobothrida manakala yang terendah ialah nematod, Ascaridia galli.